A coarse-grained model for the mechanical behavior of graphene oxide. (June 2017) - Meng, Zhaoxu; Soler-Crespo, Rafael A.; Xia, Wenjie; Gao, Wei; Ruiz, Luis; Espinosa, Horacio D.; Keten, Sinan
Abstract: Graphene oxide (GO) shows promise as a nanocomposite building block due to its exceptional mechanical properties. While atomistic simulations have become central to investigating its mechanical properties, the method remains prohibitively expensive for large deformations and mesoscale failure mechanisms. To overcome this, we establish a coarse-grained (CG) model that captures key mechanical and interfacial properties, and the non-homogeneous effect of oxidation in GO sheets. The CG model consists of three types of CG beads, representing groups of pristine sp 2 carbon atoms, and hydroxyl and epoxide functionalized regions. The CG force field is parameterized based on density functional-based tight binding simulations on three extreme cases. It accurately quantifies deterioration of tensile modulus and strength at the expense of improving interlayer adhesion with increasing oxidation of varying chemical compositions. We demonstrate the applicability of the model to study mesoscale phenomena by reproducing different force vs. indentation curves in silico, corroborating recent experimental observations on how chemistry near contact point influences properties. Finally, we apply the model to measure the fracture toughness of pristine graphene and GO. The critical stress intensity factor ( K c ) of graphene is found to be the highest, and epoxide-rich GO also possesses higher K c compared to hydroxyl-rich GO. Graphical abstract: